Endoparasites of marsupials in fragments of the Atlantic rainforest, western Paraná State, Brazil - Benatti, Danise [UNESP]; Moraes, Marcela Figueirêdo Duarte [UNESP]; Pacheco, Carmen Andrea Arias [UNESP]; Machado, Dália Monique Ribeiro [UNESP]; Oliveira, Wilson Junior [UNESP]; Perin, Patricia Parreira [UNESP]; Andrietti, Luís Felipe; Júnior, José Flávio Cândido; Vogliotti, Alexandre; Tebaldi, José Hairton [UNESP]; Hoppe, Estevam Guilherme Lux [UNESP] (FapUNIFESP (SciELO), 2023)
Knowledge of taxonomy and biodiversity of parasites is fundamental to better understand ecosystem dynamics. The objective of this study was to describe the helminth fauna of two species of marsupials in five fragments of the Atlantic rainforest in the western region of Paraná State, Brazil. In a total of 4050 trap-nights, the animals were captured using Sherman, Tomahawk, and Pitfall traps, euthanized, necropsied, and their organs inspected for helminths. After identification of the parasites, descriptors of infection, such as prevalence, mean abundance, mean intensity, and range of intensity, were calculated. Collectively, six helminth species were observed in 18 animals. The following five species were observed in Marmosa paraguayana: Viannaia hamata (58.8%), Gracilioxyuris agilisis (52.9%), Travassostrongylus sextus (17.6%), Oncicola luehei (5.9%), and Pritchardia boliviensis (5.9%). Whereas the following two species were observed in Monodelphis dimidiata: Trichohelix tuberculata (100%) and Travassostrongylus sextus (100%). This study represents a new locality record for all helminths described herein, and a new host for four helminth species. This is the first report on the helminth fauna of Monodelphis dimidiata, expanding knowledge about marsupials in the Brazilian Atlantic Forest.
Endoparasitas de marsupiais em fragmentos de Mata Atlântica no oeste do Estado do Paraná, Brasil
Keywords: Didelphimorphia; habitat fragmentation; helminths; neotropical